Relationship between green office environments toward employees' satisfaction at TNB Jengka / Nik Azma Eki Ghazali - Ghazali, Nik Azma Eki (2015)
The purpose of this research is to identify the relationship between relationship between green office environments toward employees' satisfaction At Tenaga Nasional Berhad, Jengka. This research intended to investigate the relationship of green office environment in the workplace, which about the air and noise, view and lighting and also about the friendly that can influence employees' satisfactions in the workplace. The sample size use for this study is 101 and from 101 of populations, only 55 sample size used for the actual survey based Krejcie & Morgan table for determining sample size from a given population. The questionnaire has been distributed to the random staff at TNB Jengka, Pahang and about 52 respondents have answered the questionnaires distributed. Social Science Software (SPSS) version 20 is used to analyze the results collected. Based on the finding of this research there is a significant relationship between air and noise in the workplace towards employees' satisfaction. In order to make some improvement to the employees in Tenaga Nasional Berhad, Jengka, Pahang, some recommendation for this research and recommendation for the future research was stated.